Reliable design of medical devices - Fries, Richard C. (CRC Press, 2013)
As medical devices become even more intricate, concerns about efficacy, safety, and reliability continue to be raised. Users and patients both want the device to operate as specified, perform in a safe manner, and continue to perform over a long period of time without failure. Following in the footsteps of the bestselling second edition, Reliable Design of Medical Devices, Third Edition shows you how to improve reliability in the design of advanced medical devices. Reliability engineering is an integral part of the product development process and of problem-solving activities related to manufa.
Keywords: Medical instruments and apparatus -- Reliability.; Medical instruments and apparatus -- Design and construction.; Medical instruments and apparatus -- Quality control.; Medical instruments and apparatus -- Standards.; elektronické knihy; electronic books